GE_GERICHTE A/4166/2015 vom 18. August 2016 - GE Cour de justice (2016)
RECONS; NULLE | Recours au TF interjeté le 27 mai 2016 par le débiteur, rejeté par arrêt du 18 août 2016 ( | LP.8.a.1; LP.17.4; LP.21; LP.22.1